1996
DOI: 10.1007/bf01983978
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of natural and synthetic inclusion compounds and their thermal stability

Abstract: Inclusion compounds do not belong to the group of simple compounds. They consist of molecules of the host and guest components. Some of them form supermolecules and exhibit supermolecular properties.Combinations of inclusion compounds as even more complicated systems need more methods to be used for their identification. Thermoanalytical study enables to study the sorption during their formation and the progressive liberation of their individual components and parts. Many layered silicates, phosphates and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In [2,[29][30][31]] the thermal stabilities of new inclusion compound combinations are dealt with. Morphological studies showed a changed situation after the formation of the new products prepared from clinoptilolite (CT) zeolites.…”
Section: "~149mentioning
confidence: 99%
“…In [2,[29][30][31]] the thermal stabilities of new inclusion compound combinations are dealt with. Morphological studies showed a changed situation after the formation of the new products prepared from clinoptilolite (CT) zeolites.…”
Section: "~149mentioning
confidence: 99%
“…Thermal gravimetry, TG, and differential scanning calorimetry, DSC were employed to analyse the stoichiometries and thermal stabilities of all five inclusion compounds. 9,10 The compound H•A•3B was difficult to isolate, because when the guest liquid mixture is in the mole fraction range X B 0.5-1.0, the host shows a strong propensity for the formation of H•2A•2B.…”
mentioning
confidence: 99%